COMPARISON OF CLONIDINE AND DEXMEDETOMIDINE AS ADJUVANTS TO LEVOBUPIVACAINE FOR SUPRACLAVICULAR BRACHIAL PLEXUS BLOCK IN UPPER LIMB SURGERY UNDER ULTRASOUND GUIDANCE - SINGHAL, SWATI; VISHALI, VENNAM NAGA LAKSHMI; SHARMA, S. P. (International Journal of Current Pharmaceutical Research, 2025)
Objective: The addition of adjuvants to local anesthetics can significantly improve the efficacy of regional blocks. This study compares the effectiveness of Clonidine and Dexmedetomidine as adjuvants to Levobupivacaine in a supraclavicular brachial plexus block for upper limb surgeries. Methods: This observational comparative study included 68 patients, divided into two groups to receive either Dexmedetomidine or Clonidine with Levobupivacaine. The onset and duration of the sensory block and the time to first rescue analgesia were evaluated. Results: Dexmedetomidine demonstrated a slightly faster onset and a significantly longer duration of sensory block and analgesia compared to Clonidine. Both drugs were well-tolerated without significant adverse effects. Conclusion: Dexmedetomidine surpasses Clonidine in prolonging the effects of Levobupivacaine in supraclavicular brachial plexus blocks, suggesting its advantageous use in clinical settings for extended analgesia.